Between Flesh and Spirit. Reflections on the Penitent Mary Magdalene's Iconography - Varalli , Anna (E|C, 2023)
Mary Magdalene is a mysterious and misrepresented woman, connected to the fundamental events in the life of Christ. Over the centuries, numerous superimpositions with other female characters have made her an elusive figure with nebulous boundaries, a synthesis of multiple meanings: both sinner and prostitute and converted woman and apostle. Through the study of the iconography of “Penitent Magdalene” and the semiotic analysis, the paper aims to investigate, how contrasting themes such as sin and repentance, carnality and holiness have been articulated and how they have been favourably developed in the representation of the female body and in the historical ambiguity of this character.